The science case and challenges of space-borne sub-millimeter interferometry. (July 2022) - Gurvits, Leonid I.; Paragi, Zsolt; Amils, Ricardo I.; van Bemmel, Ilse; Boven, Paul; Casasola, Viviana; Conway, John; Davelaar, Jordy; Díez-González, M. Carmen; Falcke, Heino; Fender, Rob; Frey, Sándor; et al.
Abstract: Ultra-high angular resolution in astronomy has always been an important vehicle for making fundamental discoveries. Recent results in direct imaging of the vicinity of the supermassive black hole in the nucleus of the radio galaxy M87 by the millimeter VLBI system Event Horizon Telescope and various pioneering results of the Space VLBI mission RadioAstron provided new momentum in high angular resolution astrophysics. In both mentioned cases, the angular resolution reached the values of about 10–20 microarcseconds (0.05–0.1 nanoradian). Further developments towards at least an order of magnitude "sharper" values, at the level of 1 microarcsecond are dictated by the needs of advanced astrophysical studies. The paper emphasis that these higher values can only be achieved by placing millimeter and submillimeter wavelength interferometric systems in space. A concept of such the system, called Terahertz Exploration and Zooming-in for Astrophysics, has been proposed in the framework of the ESA Call for White Papers for the Voyage 2050 long term plan in 2019. In the current paper we present new science objectives for such the concept based on recent results in studies of active galactic nuclei and supermassive black holes. We also discuss several approaches for addressing technological challenges of creating a millimeter/sub-millimeter wavelength interferometric system in space. In particular, we consider a novel configuration of a space-borne millimeter/sub-millimeter antenna which might resolve several bottlenecks in creating large precise mechanical structures. The paper also presents an overview of prospective space-qualified technologies of low-noise analogue front-end instrumentation for millimeter/sub-millimeter telescopes. Data handling and processing instrumentation is another key technological component of a sub-millimeter Space VLBI system. Requirements and possible implementation options for this instrumentation are described as an extrapolation of the current state-of-the-art Earth-based VLBI data transport and processing instrumentation. The paper also briefly discusses approaches to the interferometric baseline state vector determination and synchronisation and heterodyning system. The technology-oriented sections of the paper do not aim at presenting a complete set of technological solutions for sub-millimeter (terahertz) space-borne interferometers. Rather, in combination with the original ESA Voyage 2050 White Paper, it sharpens the case for the next generation microarcsecond-level imaging instruments and provides starting points for further in-depth technology trade-off studies. Highlights: Microarcsecond angular resolution is a key for pioneering discoveries in astronomy. Microarcsecond sharpness in astronomy can only be achieved by telescopes in space. Space interferometry at terahertz frequencies - a unique gateway for new science. In-orbit assembly – a new approach for creating large spaceborne telescopes.